The importance of coagulation factors binding to adenovirus: historical perspectives and implications for gene delivery. (November 2014) - Lopez-Gordo, Estrella; Denby, Laura; Nicklin, Stuart A; Baker, Andrew H
<x xml:space="preserve">Abstract</x> Introduction: The interaction of human adenovirus (HAdV) serotype 5 (HAdV-5) with the blood coagulation factor X (FX) results in a high liver transduction after AdV intravascular administration, causing toxicity and limiting AdV delivery to the target tissue. However, FX also protects adenoviral vectors from neutralization by the complement system and natural antibodies, potentially benefiting adenoviral gene delivery, as neutralization results in the reduction of HAdV-5 binding to host cells. Areas covered: This review gives an overview on the use of adenoviruses as gene transfer vehicles and their impact in gene therapy. The structure of coagulation factors and their interactions with HAdV are described, highlighting their influence on the AdV biodistribution profile. The implications of this interaction in immunity and its potential influence on the use of adenoviral vectors in gene therapy applications are discussed. Expert opinion: The protective role of FX brings under discussion how beneficial abolishment of FX binding would be for HAdV-5 liver detargeting. The dispensability of FX for liver transduction in immunocompromised mice suggests the involvement of other blood factors or receptors in enhancing HAdV-5 liver transduction. Better understanding of the interactions that take place in the bloodstream is essential to generate safe and efficient adenoviral vectors.